Enrichment of highly pure large-diameter semiconducting SWCNTs by polyfluorene-containing pyrimidine ring. Issue 56 (14th October 2019) - Wei, Xia; Maimaitiyiming, Xieraili
Abstract : The pyrimidine- alt -fluorene copolymer exhibits excellent selectivity towards the semiconducting SWCNTs, and the methylated pyrimidine ring presents a better performance. Abstract : The use of copolymers to extract and purify semiconducting SWCNTs (sc-SWCNTs) and metallic SWCNTs (m-SWCNTs) is widely employed. In this paper, the performances of two pyrimidine- alt -dioctylfluorene conjugated polymers in the enrichment of semiconducting SWCNTs are compared, and the subtle structural effects on them are discussed. It was found that both pyrimidine-polymers were more effective in wrapping the semiconducting SWCNTs than the metallic SWCNTs under the co-action of the pyrimidine and fluorene rings. Moreover, methyl groups on the pyrimidine ring of the polymer slightly contributed to the semiconducting purity, and the minor differences of sc-SWCNTs extraction between two pyrimidine-polymers are compared. Additionally, the average diameter of the selected SWCNTs is larger than that of the raw SWCNTs. The experimental results show the excellent selectivity for sc-SWCNT from both co-polymers: the index Φ i values for determining the purity of sc-SWCNTs were increased from 0.408 for P2 to 0.465 for P1, of which the selected sc-SWCNT purity is up to 99.9%. The resulting purity and the inexpensive availability of pyrimidine co-polymers make them suitable to be considered for effective sc-SWCNT enrichment.